Feeding habits of the threatened aquatic Andean frog Telmatobius rubigo (Anura: Telmatobiidae) - Akmentins, Mauricio Sebastián (2020)
The aquatic Andean frogs of the genus Telmatobius have evolved closely with the aquatic ecosystems of the Andes of South America. The Laguna de Los Pozuelos’ Rusted Frog (Telmatobius rubigo) is a Threatened and endemic species of the Central Andean Puna ecoregion in Argentina. This species has a specialized feeding mechanism which relies on the inertial suction of prey, but our knowledge about its natural history is still incomplete. This study examined the feeding habits of T. rubigo by the stomach fushing technique. The relevance of the registered prey items was assessed using the dietary importance value index, and the relationship between frog body size and prey volume was determined. In total, 189 prey items were identifed in 29 stomach content samples, reaching a representative number of diet samples for this species. Telmatobius rubigo had a fully aquatic diet, with a clear predominance of adult aquatic coleopterans, immature stages of benthic insects, and crustaceans; and a high incidence of non-nutritive elements (sand and vegetation debris) was also found in the stomach contents. The results indicate that the species exhibits generalist feeding habits, and the volume of consumed prey items is positively related to the body size of the frogs. We suggest that the species develops mainly an active search mode of their benthic prey. This study represents one of the most complete dietary records for a Telmatobius species, and helps us to understand the ecology of this species in the extreme desert environment of the high Andes Puna. These results can contribute to the conservation efforts being made for Telmatobius species.